THE EARLY WRITINGS OF MADHUSUDAN DUTTA: A CRITICAL ANALYSIS - Sau, Sudipta (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Dutta was a prolific writer and a poet. His early works include ‘The Captive Ladie’ (1849) and ‘The Anglo-Saxon and the Hindu’ (1854). In his early literary career, Dutta exclusively wrote in English, a decision that can be contextualized within the British colonial education system in India. The poem is set against the backdrop of a well-known historical event in India: the expedition of Mahmud of Ghazni and subsequent political dynamics among Indian rulers. Macaulay’s advocacy for the promotion of English literature and education in India had a profound impact on his contemporaries, who found themselves at the crossroads of multiple cultural influences.